Strategy For Productive Use of Waqf Funds to Improve Musahik Welfare: (Analysis Study: Mandiri Sociopreneur Center Sari Rogo Sidoarjo) - Ainun Rosydah; Dewi Riza Lisvi Vahlevi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Waqf is a process of giving assets from someone to the people to benefit from them while still preserving the substance, therefore it is called almsgiving, and waqf is also included in ijtimaiyah worship (social worship).Waqf functions for the wakif as an investment in the world of the afterlife that will never end, and for the people as a source of eternal funds that grow cumulatively for the public interest. Productive management of waqf is still relatively small. As happened in Sari Rogo Village, Sidoarjo Regency. In this village, productive waqf is managed by exploiting the potential that exists in Sarirogo village, where the majority of the community has agricultural land, so a small portion of the community donates their rice fields which is used as additional funds for maintaining the existing waqf. However, all proceeds from the management of the rice fields are only given to the mosque as assets for the welfare of the mosque. For this reason, the potential of rice waqf as a means of empowering the community in Sari Rogo Village has not been managed optimally and empowered optimally. Waqf in the form of rice fields is the focus of this research because rice field waqf is a type of productive waqf which, if managed well, will provide better benefits than consumptive ones. In this research there are several problem formulations as follows: 1 . What is the impact of productive waqf management in improving the welfare of the people? 2. This research uses a qualitative descriptive method, namely describing the manager (nazir), management and allocation of productive waqf proceeds, in this case focused on the productive waqf management strategy in the productive waqf institution of Sari Rogo village, Sidoarjo. The information that the author obtained used interview, observation and documentation methods. Data management is carried out using editing, coding and tabulation methods, then using deductive thinking methods to obtain specific conclusions.